ADVERSITY QUOTIENT (AQ) DAN STRES KERJA PEGAWAI BAGIAN PROTOKOL PEMERINTAH PROVINSI JAMBI - Kurniawan, Imam; Krisnawati, Ema (Jurnal Studia Insania, 2019)
A precedence employee works not only in the office but also in the field. Fieldwork sometimes makes scheduled jobs changed at any time. This happens when a government leader visits the office. In that case, the precedence officer is obliged to facilitate all the attending guests to the event. This condition requires precedence employees to be available 24 hours a day. The number of jobs that must be completed in a short time can cause work stress on precedence employees. There are several ways to reduce work stress, such as having reasonable confidence, high work motivation, and adversity quotient. The ability of Adversity Quotient (AQ) is an individual's ability to face adversity and turn it into a challenge. The data retrieval techniques employed used the adversity quotient scale from Stoltz theory (2003) and work stress scale from Robbins theory (1996). The analysis technique in this research used by Pearson product-moment. The results of this study showed a significant correlation between adversity quotient and job stress (r = -0.426, p = 0.019). This study shows the level of work stress will be reduced if the precedence employees have a high Adversity quotient.